2019
DOI: 10.17219/acem/94065
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-3 levels in relation to disease activity and radiological progression in rheumatoid arthritis

Abstract: Background. Rheumatoid arthritis (RA) is a chronic inflammatory and systemic disease of unknown etiology that primarily affects synovial joints and involves progressive destruction around the joints. Inflammation starting in the joint synovium causes the destruction of cartilage, bone and other adjacent tissues with pannus formation. Objectives. The aim of this study was to evaluate serum matrix metalloproteinase-3 (MMP-3) levels and their clinical and radiological significance in patients with rheumatoid arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
3
21
1
Order By: Relevance
“…In RA and experimental arthritis, the family of MMPs plays not only an important role in the proteolytic cleavage of articular cartilage but also of the extra-cellular matrix (ECM) of the synovial joints (43). MMP-3 is known to degrade CII, the predominant form of collagen in articular cartilage (44), whereby MMP-3 concentrations are elevated in serum of humans and mice with active arthritis (45,46). In our CIA experiments, there was a trend towards lower MMP-3 serum concentrations at day 47 in the etanercept group compared to the PBS group and the difference was statistically significant when comparing the etanercept group with the C21 group.…”
Section: C21 Reduces Inflammation and Prevents Cartilage Loss In Ciamentioning
confidence: 99%
“…In RA and experimental arthritis, the family of MMPs plays not only an important role in the proteolytic cleavage of articular cartilage but also of the extra-cellular matrix (ECM) of the synovial joints (43). MMP-3 is known to degrade CII, the predominant form of collagen in articular cartilage (44), whereby MMP-3 concentrations are elevated in serum of humans and mice with active arthritis (45,46). In our CIA experiments, there was a trend towards lower MMP-3 serum concentrations at day 47 in the etanercept group compared to the PBS group and the difference was statistically significant when comparing the etanercept group with the C21 group.…”
Section: C21 Reduces Inflammation and Prevents Cartilage Loss In Ciamentioning
confidence: 99%
“…Matrix metalloproteinase-3 (MMP-3) is a proteolytic enzyme induced by inflammatory cytokines and is used as a serum indicator of RA activity; it plays a central role in progressive joint destruction in RA and thus is attracting attention as a marker for predicting joint destruction. 10 , 11 Tuncer et al 12 reported significantly higher MMP-3 levels in patients with RA with high DASs. Furthermore, MMP-3 levels increase with Steinbrocker stage and class, indicating RA severity.…”
Section: Introductionmentioning
confidence: 98%
“…But later ndings indicated that elevated levels of VEGF were also characteristics of infections and organizing pneumonia in RS 3 PE [9,10] . MMP-3 was elevated in RS 3 PE patients with solid malignancy [11] , but it was also an indicator for active arthritis [12] . It still remains elusive whether there is a speci c biomarker for identifying arthritis with malignancy.…”
Section: Introductionmentioning
confidence: 98%